Optimum Friction Level of a Randomly Excited Beam with Hysteretic Boundary Supports - Hallajisani, S.; Kashani, H.; Nobari, A.S. (Journal of Applied Nonlinear Dynamics, 2026)
This paper investigates the behaviour of frictional bolted supports that are example of boundary conditions exhibiting nonlinear stick-slip phenomena and act as bilinear hysteretic systems which is modelled here by Jenkins frictional element. An Euler-Bernoulli beam containing bolted supports under white noise excitation is considered. The dependence of equivalent damping and variance of the response amplitude to joint stiffness, sliding threshold and input intensity are identified and optimum sliding threshold is obtained to have minimum overall variance of system response. Further, the Monte-Carlo simulation is developed to verify the results and shown that when the Jenkins stiffness is big enough, the Linearization technique and Monte-Carlo simulation are in good agreement.